Scenario Forecasting of the Reproduction Process in the Agriculture in View of Inflation - BAYDAKOV, Andrey N.; CHERNIKOVA, Lyudmila I.; NAZARENKO, Anton V.; ZAPOROZHETS, Dmitry V.; SIDOROVA, Darya V. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
The article views the contradiction between competitiveness of agricultural organizations in the modern economic conditions, which are characterized by sustainable rates of creeping inflation and the impossibility for recreation of the totality of resources due to the macro-economic instability. The analysis showed a lot of drawbacks of the existing approaches and methods to evaluation of effectiveness of the reproduction process of the agrarian sector of economy. That’s why, for the purpose of studying the dynamic characteristics of the reproduction processes in agriculture of Stavropol Krai, a system of equations was build, which supposes each of the equations system’s parameters belonging to a certain interval, determined on the basis of statistical data or by expert evaluation. This predetermined the expedience of using the scenario forecasting. Each of the formed scenarios received hypersurfaces of change of the coefficient of the fixed production assets renovation intensity in time, which reflect a substantial non-linear interconnection between the reproduction and inflation tendencies. Based on the results of the performed research, each level of the sphere management was assigned a system of measures, including the supporting measures – in the conditions of implementing the optimistic scenario of the reproduction process development, and correcting measures – in the conditions of the pessimistic scenario of the reproduction process development.